Growth and chemical functionalization of SiC nanowires for biomedical applications in cardiology and oncology - Quaretti,Martina (Department of Chemistry, 2023)
The current leading causes of death in the world are cardiovascular diseases (in particular myocardial infarctions) and cancer. In Italy in 2016 almost 400,000 people died because of these two pathologies. Despite the great progress made by medicine in recent decades, the road to cure these diseases is still long, and cancer and cardiac diseases remain a serious socio-economic problem for our society. For this reason, this PhD research focuses on these two main topics; called in the thesis the oncology project and the cardiology project. Both projects were devoted to the synthesis of Silicon Carbide Nanowires (SiC NWs), aiming to devise their new possible biomedical applications in the field of oncology and cardiology. This PhD, funded by Cariparma Crédit Agricole, is part of a Bilateral Agreement for Joint Philosophy Doctor (PhD) Degrees between the University of Parma and CNR-IMEM with the University of Cape Town. The synthesis of compounds for potential applications in cancer treatment was the main research topic of the oncology project during the period spent abroad in South Africa. Modern anti-tumor therapies are very invasive for the patient and often based on the administration of drugs, generally cisplatin derivatives, very cytotoxic and harmful to the human body. Furthermore, such treatments are often not fully selective and kill the diseased but also the healthy cells of the organism. Therefore, the aim of many scientists in the world is to design and synthesize new molecules with excellent anticancer properties but with fewer side effects compared to the drugs already currently in use, for example, less toxicity and greater selectivity for the cancer cells. Thiosemicarbazones (TSCs) are Schiff bases which in recent years have attracted considerable attention thanks to their promising anticancer properties. These compounds are very active also in the fight against malaria, moreover they are used as antifungal and antibacterial agents. TSCs are widely documented in literature, and a correlation has often been found between the efficacy of the antitumor activity of the molecule and the presence of aromatic groups in its structure. Furthermore, exploiting the presence in the TSCs of a set of donor atoms (N and S) able to coordinate various types of metal ions to form the related complexes, many studies emphasize the importance of the presence of metal ions bound to the molecule to further increase the antitumor efficacy. Unfortunately, TSCs have poor solubility in aqueous matrices. This behavior can make their administration as drugs more complex and create possible problems of precipitation (due to the insolubility) or accumulation inside the human body. For this reason, in the oncology project of this PhD research a series of aromatic-TSCs were synthetized and then anchored on the chemically modified surface of SiC NWs, employed as carriers. According to previous results obtained by my research group at IMEM-CNR, these SiC-based NWs are biocompatible and can be conjugated with several organic molecules (e.g. porphyrins). The target of these new nanomaterial-drug systems are solid tumors, e.g. affecting breast, lungs, pancreas and liver, where they can be injected and be active to reduce the tumor mass in view of later surgical removal. To anchor these thiosemicarbazones to the nanowires, SiC NWs coated with a thin external layer of silica (nanomaterials called core-shell SiC/SiO2 NWs) were chosen. In fact, this external layer of silica can be chemically functionalized by appropriate silane linkers. The silane linkers used are (3-aminopropyl)triethoxysilane (APTES) and triethoxy(3-isothiocyanatopropyl) silane (Si-NCS). These alkoxysilanes react with the silica surface and covalently bind to the NWs. Thus, it was possible introduce on the NWs surface amino or isothiocyanate groups, able to react with proper TSCs in the anchoring step. To conjugate the NWs with TSCs, it was required the synthesis of thiosemicarbazones having suitable functional groups able to react with the groups present on NWs surface. In this way thiosemicarbazone molecule was anchored by covalent bonds to the surface of the nanowires. During the time spent at the University of Cape Town, working on the oncology project, various TSCs-metal complexes were prepared and successively anchored to NWs previously decorated with amino groups. Literature is rich in examples of platinum (and related metals) complexes with excellent anticancer activity. Therefore, reactions between the TSCs bound to the NWs surface and platinum, ruthenium and rhodium salts were carried out to obtain NWs functionalized with these complexes. Unfortunately, it was observed that this approach has a drawback due to the ability of the amino groups to give competitive complexes with transition metals. Therefore, the attention of the oncology project was focused on a specific thiosemicarbazone compound (Triapine), on a way to find a new procedure to anchor it to NWs and subsequently on the evaluation of the antitumor activity of this new nano-system by in vitro tests. Triapine is an α-(N)-heterocyclic thiosemicarbazone, which successfully passed Phase II of Clinical Trial. Currently, Triapine is tested as an anticancer drug in human patients. The precursor of Triapine was synthetized, with a suitable functional group able to react with the Si-NCS linker anchored to the NWs. In this way the NWs surface was covered by Triapine molecules connected to the SiC/SiO2 structure through a carbon chain as linker. Then, the anchored Triapine was used as a ligand to coordinate metal ions; specifically copper, a metal with low toxicity to the human body. Subsequently, these nano-systems (NWs-Triapine and NWs-Triapine-Cu complex) and the free molecules (Triapine and Triapine-Cu complex without NWs) were tested on A549 human lung adenocarcinoma cell line to evaluate their antitumor efficacy. The free molecules showed good IC50 values – in the micromolar range - with greater antitumor activity of the free complex compared to the free ligand in the first 24 h, but situation reversed in the subsequent 48 h and 72 h. Vice versa, about the compounds anchored to the NWs, only the NWs-complex has proved active, suggesting that the free molecules and the molecules anchored to the NWs have different mechanisms of action and different interactions with cancer cells. The mechanisms of action were better investigated studying the cell cycle. Regarding the other research topic of this PhD thesis, the problem of myocardial infarction has been addressed in the cardiology project. Infarction is the death (necrosis) of part of the heart muscle tissue (myocardium) due to the lack of adequate oxygenation by the arterial blood flow (ischemia). After the infarction, the affected area is no longer able to contract due to the death of cardiomyocytes, the cardiac cells responsible for the generation and transmission of the electro-cardiac pulse. The dead cardiac cells cannot be regenerated and are replaced by a fibrous connective tissue (collagen fibers) that forms a scar area in which the electrical pulse is no longer able to be diffused. Therefore, an insulating area is generated in the heart, with drastic consequences for the health of the organ and for the correct cardiac functioning. Previous in vitro experiments on cardiomyocytes had shown that SiC NWs (semiconductive nanowires, without the external shell of silica) were able to connect two distant cardiac cells, previously isolated from each other. Thanks to the presence of SiC NWs, the two cells, previously silent, were able to propagate the electric pulse to each other and to synchronize their action potential. Based on these results, in collaboration with a medical research team of the University of Parma, in this cardiology project SiC NWs were tested in vivo on infarcted rats' hearts, to verify if the SiC NWs semiconductive properties were able to restore, even partially, the normal propagation of the cardiac electrical pulse, interrupted after the infarction in the ischemic tissues area. For this purpose, in ten rats the myocardial infarction was induced by creating an ischemic zone in the left ventricle through three different protocols: injection of formaldehyde solution at different concentrations (4% and 38%), deposition of a drop of formaldehyde 38% solution on the heart surface and cryoinjury (creation of a necrotic area by selective burning of cardiac tissues using a metal tip cooled by liquid nitrogen). Before and after the infarction the electro-cardiac activity was monitored with a special high-resolution electrode grid. This accurate epicardial mapping of the affected area showed important changes in the values related to the EGs parameters (waves and intervals) and in the isochrone maps (velocity and direction of propagation of the pulse wavefront) before and after the infarction. These data also allowed to understand that cryoinjury was the best technique in creating an effective ischemic zone, with well-defined edges, easily reproducible in rats. Subsequently, a saline solution containing SiC NWs was injected into the infarcted area and the cardiac signals were collected and analyzed. The aim of this cardiology project is to compare the cardiac functioning after the injection of semiconductive SiC NWs with the pre-infarction conditions to evaluate whether the use of SiC NWs helps restore normal cardiac functioning, lost as a result of a myocardial infarction. Based on preliminary data, in some rats after the injection of SiC NWs some important physioelectric parameters show promising changes compared to the values recorded after the infarction, returning similar to the normal pre-infarction conditions. However, the absence of significant statistical series makes it difficult to assert more specific statements.